2020
DOI: 10.1038/s41467-020-19801-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced efficacy of HIV-1 integrase inhibitors in patients with drug resistance mutations in reverse transcriptase

Abstract: Little is known about the impact of pretreatment drug resistance (PDR) on the efficacy of second generation integrase inhibitors. We sequenced pretreatment plasma specimens from the ADVANCE trial (NCT03122262). Our primary outcome was 96-week virologic success, defined as a sustained viral load <1000 copies/mL from 12 weeks onwards, <200 copies/mL from 24 weeks onwards, and <50 copies/mL after 48 weeks. Here we report how this outcome was impacted by PDR, defined by the World Health Organization (WHO)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 50 publications
3
49
1
Order By: Relevance
“…For the 68% of participants with VF while on DTG/INSTI based regimens but devoid of INSTI DRMs, we did not assess for other mutations in nef, reverse transcriptase and protease genes that could contribute to VF [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…For the 68% of participants with VF while on DTG/INSTI based regimens but devoid of INSTI DRMs, we did not assess for other mutations in nef, reverse transcriptase and protease genes that could contribute to VF [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study established that drug susceptibility and viral fitness may be affected by potential cross-class mutational interactions. Siedner et al observed that non-nucleoside reverse transcriptase inhibitor resistance before treatment with HIV-1 integrase inhibitors is associated with the long-term failure of integrase-inhibitor-containing first-line regimens [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, long term use of DTG is still under concern (Kouanfack et al, 2019 ; Bourgi et al, 2020 ; Sax et al, 2020 ). A recent communication in December 2020 by Siedner et al found that patients with drug resistant mutation in the reverse transcriptase are unlikely to benefit from the HIV integrase inhibitor DTG (Siedner et al, 2020 ). That implies EFV and NVP might still be in use for specific group of patients (Vitoria et al, 2018 ).…”
Section: Population Disparity In the Use Of Cyp2b6 Substrates And Consequent Exposure To Substrate-specific Adverse Drug Reaction (Adr)mentioning
confidence: 99%